Fucoidan từ rong nâu Sargassum swartzii: phương pháp tách, hoạt tính gây độc tế bào ung thư và nghiên cứu cấu trúc - Cường và cộng sự, Nguyễn Mạnh (Vietnam Journal of Chemistry, 2014)
The brown seaweed Sargassum swartzii was extracted with hydrochloric acid solution, dialyzed through a 1K MWCO membrane and precipitated by Cetavlon to yield polysaccharides. The polysaccharides were dissolved in calcium chloride solution, precipitated in ethanol for obtaining the crude fucoidan (F-SS). The crude fucoidan was fractionated with sodium chloride solution of 0.5, 1.0, 1.5, 2.0 and 2.5 M yielding six fucoidan fractions F05, F10, F15, F20, F25, respectively. The composition of fucoidan fractions including monosaccharides, sulphate, uronic acids and total carbohydrate was analyzed. The distribution of molecular weight of the fucoidan fractions was studied. Ninety percents of both F20 and F25 fractions have the average molecular weight of over 100 kDa. Fraction F-20 showed significant activity against human Rhabdosarcoma cells with an IC50 value of 16.6 mg/mL and lung cancer cells of 13.4 mg/mL. Fucoidan F25 was against only lung small cancer cells with an IC50 value of 13.8 mg/mL.